STIMULATION ATTITUDIONAL REFLEX EXERCISE LEBIH BAIK DIBANDINGKAN DENGAN PRONE POSITION WEDGE EXERCISE TERHADAP HEAD CONTROL PADA ANAK CEREBRAL PALSY SPASTIK QUADRIPLEGI DI RS RAJAWALI CITRA BANTUL, YOGYAKARTA - Al Banna, Damha; Adiatmika, I Putu Gede; Irfan, M.; Griadhi, I Putu Adiartha; Sundari, Luh Putu Ratna; -, Sugijanto (Sport and Fitness Journal, 2019)
ABSTRACT Background: Head control is a disorder of the cerebral palsy (CP) spastic quadriplegi due to central nervous system problems that serve as the basis of movement to be achieved for further development. Physiotherapy actions that can be given are stimulation attitudional reflex exercise (SARE) and prone position wedge exercise (PPWE). Purpose: This study aims to determine whether SARE is better than PPWE for head control in CP spastic quadriplegi. Methods: This research uses experimental pre and post test control group design is done at Rajawali Citra Bantul Hospital. Subjects were 24 children with CP spastic quadriplegi divided into 2 groups, group I was given SARE for 3 repetitions in 1 hour of therapy sessions and group II was given PPWE for 30 minutes. All groups were given treatment 1 time a week for 6 weeks as a refresher intervention and educated the family to do every day at home. Increased head control is measured by gross motor functional measurement. Result: Statistical test of paired sample t-test in group I and group II p value = 0.001 where (p < 0.05) there was an increase of head control. From independent t-test p value = 0.001 where (p < 0.05), it can be concluded that there are significant differences between group I with group II. Based on the mean values in both treatment groups, the group I have larger head control improvement of 33.19% than group II which only 16.96%. Conclusion: SARE is better than PPWE to increase head control on CP spastic quadriplegi Keywords: Head control, SARE, PPWE